Understanding Richard Hoggart : a Pedagogy of Hope - Bailey, Michael; Clarke, Ben.; Walton, John K. (Hoboken : John Wiley & Sons, 2011)
With the resurgent interest in his work today, this is a timely reevaluation of this foundational figure in Cultural Studies, a critical but friendly review of both Hoggart's work and reputation. Re-examines the reputation of one of the & lsquo;inventors & rsquo; of Cultural StudiesUses new archival sources to critically evaluate Hoggart's contribution and influence, set his work in context, and determine its current relevanceAddresses detractors and their positions of Hoggart, delineating long-term ideological battles within academiaBrings cultural studies, literary criticism, and social history.
6 Policy, Pedagogy, and IntellectualsAn International Servant; The Idea of University Adult Education; The Role of the Intellectual; Index.
Print version record.
Keywords: Hoggart, Richard, -- 1918-2014.; Hoggart, Richard, -- 1918-2014.; Critics -- Great Britain -- Biography; Intellectuals -- Great Britain -- Biography; Hoggart, Richard, 1918-; Social Science; Literature; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Popular Culture; Critics; Intellectuals; Great Britain; Electronic books; Biography